LEGAL ASSURANCE OF MATERIAL RIGHT IN THE PROPERTY RIGHT OF FLAT UNIT - Martin, Abraham Yazdi (Magister Ilmu Hukum Sekolah Pascasarjana Unida, 2017)
Guarantees of material rights are collateral held by a creditor against one item whereby the right owned by the owner on the item is affixed to the priority right owned by the creditor so that it can be given a repayment first by selling the secured item for a debt. The practice of property law in society has developed with the new right in the legal system of objects, which is called the right of property of the apartment unit (HMSRS) or also known as strata-title. Most of the flats (commercial flats) are built on building rights, since building use rights are generally owned by Limited Liability Company (developers) who can only own building rights in accordance with the provisions of Basic Agrarian Law (UUPA). The issue becomes uncertain when the tenure period ends, while the title given to the flats is a property that does not recognize the ending period as a result of HMSRS ownership registration using the vertical sticking principle. This study aims to analyze and simultaneously provide a solution to the problem of property law in Indonesia, especially regarding the legal certainty of the material with the approach of normative juridical and sociological juridical support that sees legal postulates in the application of property law.Keywords: material rights, property law, vertical access principle, fiducial law